Empirical study on the impact of management forecast errors on IPOs underpricing and market reaction to post-listing earnings announcements. - Lee, Sok Mui. (2008)
In this paper, we examined empirically the role played by the public disclosure of management forecasts in the pricing of (IPOs) and the market reaction to these forecast errors.